Comparison of malignancy and spatial distribution between latent and clinical prostate cancer: an 8-year biopsy study - Zhen, Liang; Zhien, Zhou; Hanzi, Huang; Xingcheng, Wu; Yu, Xiao; Wenze, Wang; Yuzhi, Zuo; Yuliang, Chen; Yi, Zhou; Weigang, Yan (European journal of medical research, 2022)
Background Current prostate cancer (PCa) screening may detect nonprogressive lesion, leading to overdiagnosis and overtreatment. The purpose of the present study is to investigate whether the tumor pathological origin of latent prostate cancer (lPCa) and clinical prostate cancer (cPCa) are consistent, and to verify the current clinically significant prostate cancer criteria. Methods Prostate specimens were obtained from postmortem autopsy between 2014 and 2021 and patients who went through radical prostatectomy from 2013 to 2021. The pathological characteristics and spatial distribution of the lPCa group and cPCa group were compared and analyzed through SPSS software with P < 0.05 representing statistical significant. Results In lPCa group, a total of 45 tumor lesions from 24 lPCa cases were included, 54.2% of lPCa patients were ISUP [greater than or equal to] 2, 12.5% had tumor volume [greater than or equal to] 0.5 ml, and 16.7% had extraprostatic extension (EPE). In cPCa group, there were a total of 429 tumor lesions in 126 cases, 92.1% of cPCa patients were ISUP [greater than or equal to] 2, and 82.5% had tumor volume of [greater than or equal to] 0.5 ml. 36.3% had EPE. LPCa and cPCa have the same spatial distribution characteristics, and no significant difference was detected between the anterior and posterior zone. Peripheral zone tumors were significantly more common than transitional zone tumors. Tumors in apical 1/3 and middle 1/3 were significantly more common than basal 1/3. Conclusion The malignancy of cPCa is significantly higher than that of lPCa, and the spatial distribution of cPCa and lPCa is consistent. ISUP grade 2 is not sufficient to determine clinical significance of tumor. Keywords: Autopsy, Latent cancer, Prostate cancer, Spatial distribution, Malignancy